The influence of mobile payments on the choices and functionings of Micro and Small Enterprise (MSE) entrepreneurs in Lesotho - Hlabeli, Batloung (Department of Information Systems, 2021)
Background: This study explores the significance of ICT on the capabilities of unbanked MSE entrepreneurs in Lesotho. MSE entrepreneurs are the primary source of income for their families, especially in the context of developing countries. Accordingly, MSEs are fundamental instruments for economic growth, poverty alleviation and source of employment in developing countries. Hence, the country that invests in this business sector is a step closer to accomplishing its MDGs. Purpose: The study explored and empirically assessed the influence of mobile payments among MSE entrepreneurs through a capabilities lens. Given that MSEs are crucial for developing countries, the targeted participants were MSE entrepreneurs from diverse trading industries in Lesotho. Research methodology: The methodology for this study was qualitative. Exploratory and descriptive research methods were used to evaluate the influence of mobile payments on the capabilities of MSE entrepreneurs. This study adopted Kleine's Choice Framework to explore and empirically assess the benefits of mobile payments among MSE entrepreneurs. Data was collected using semi-structured interviews and field notes and analysed using thematic analysis. Key Findings: The findings revealed the use of M-Pesa within the MSE sector enabled microentrepreneurs to accomplish their goals. The findings show that M-Pesa leads to the growth of MSEs. Therefore, entrepreneurs in the MSE business sector are capable of providing food, shelter and clothes for their families through income generated from their enterprises. Additionally, MSE entrepreneurs bank, transfer and receive money through accessible and available mobile payment platforms. However, these entrepreneurs face issues such as network failure, withdrawal amount limits and security risks while using mobile payments. Value of the study: The study contributes to the existing ICT4D and mobile payments literature in Lesotho by discussing the influence of mobile payment through the Choice Framework.